2023
DOI: 10.9755/ejfa.2022.v34.i12.2977
|View full text |Cite
|
Sign up to set email alerts
|

Technological quality of wheat grains and flour as affected by nitrogen fertilization and weather condition

Abstract: The quality of grains and flour can be influenced by genetics, crop management, and environment. The objective of this study was to evaluate the technological quality of wheat grains and flour influenced by the interaction among genotype, nitrogen (N) fertilization and weather conditions in different regions of wheat crop adaptation in southern Brazil, aiming to support farmers and the bakery industry sector in their decision-making processes. The experiment was carried out in three environments (Londrina in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(107 reference statements)
1
0
0
Order By: Relevance
“…Despite the study revealing no significant effect of the interaction between nitrogen and variety on several parameters, it offers crucial insights. The consistent reaction of various wheat varieties to nitrogen fertilization among the genotypes is consistent with prior studies, which have shown comparable responses in wheat genotypes [45,46]. This consistency suggests that the nitrogen effect is independent of variety type.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the study revealing no significant effect of the interaction between nitrogen and variety on several parameters, it offers crucial insights. The consistent reaction of various wheat varieties to nitrogen fertilization among the genotypes is consistent with prior studies, which have shown comparable responses in wheat genotypes [45,46]. This consistency suggests that the nitrogen effect is independent of variety type.…”
Section: Discussionsupporting
confidence: 89%